Private participation in infrastructure in China : Issues and recommendations for the road, water, and power sectors - Bellier, Michel; Zhou Yue Maggie (Washington, D.C.: World Bank, 2003)
This report seeks to improve China's approach to private participation in infrastructure. It also compares China's experiences with those of other countries.
World bank working paper No. 2
Includes bibliographical references
osa 23/9/16
Loans
Keywords: Infrastructure (Economics); Investments - China; China